Thorax high resolution computerized tomography findings in asthmatic children with unusual clinical manifestations - (:unkn) unknown (AMER COLL ALLERGY ASTHMA IMMUNOLOGY, 1999)
Background: It has been consistently observed in high resolution computerized tomography (HRCT) scans that asthmatic patients manifest more abnormalities related to airways remodeling than do normal subjects. Objective: To find the underlying abnormalities in the lungs of asthmatic children with unusual manifestations. Method: Asthmatic children not responding as expected to inhaled steroid therapy with or without localized permanent or temporary recurrent auscultation findings (rales) were evaluated with chest radiographs and HRCT scans. Bronchoscopy was performed on the ones with localized rales. Results: The sample consisted of 26 asthmatic children (6 girls and 10 boys, mean age = 7.75 +/- 4.43 years). Chest radiograph abnormality rate was 44% and the thorax HRCT scan abnormality rate was 75% (56% fibrotic retractions, 38% atelectasis, 19% bronchiectasis, and 19% bronchial wall thickening). Two patients with localized permanent rales and with right middle lobe (RML) atelectasis in HRCT scan underwent bronchoscopy which revealed RML syndrome due to mucus plugging in one and lymph node pressure in the other. In one patient with localized temporary recurrent rales and major bronchiectasis in HRCT scan, bronchoscopy revealed bronchitis. The patient with RML syndrome due to mucus plugging required lobectomy. Conclusion: We conclude with this experience that thorax HRCT scanning may be a helpful adjunct in the evaluation of an asthmatic children with atypical clinical findings.
Keywords: LUNGS; DISEASE